2009
DOI: 10.2174/138955709788167619
|View full text |Cite
|
Sign up to set email alerts
|

EGF Receptor as a Drug Target in Arterial Hypertension

Abstract: Drugs which inhibit epidermal growth factor receptor (EGFR) are used in the treatment of cancers. EGFR may contribute to the development of hypertension by regulating vascular tone and renal Na+ handling. Synthetic EGFR inhibitors reduce blood pressure in some experimental models of hypertension suggesting that this receptor is a novel target for antihypertensive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 95 publications
(119 reference statements)
0
14
0
1
Order By: Relevance
“…EGFR is a plasma membrane tyrosine kinase which may be activated by its cognate ligand, epidermal growth factor (EGF), and several other proteins like heparin-binding epidermal growth factor (HB-EGF) [37, 38]. EGFR is highly expressed in renal tubules and its peptide ligands are abundant in urine.…”
Section: Pparγ-c-src-egfr-erk Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…EGFR is a plasma membrane tyrosine kinase which may be activated by its cognate ligand, epidermal growth factor (EGF), and several other proteins like heparin-binding epidermal growth factor (HB-EGF) [37, 38]. EGFR is highly expressed in renal tubules and its peptide ligands are abundant in urine.…”
Section: Pparγ-c-src-egfr-erk Pathwaymentioning
confidence: 99%
“…However, apart from its ligands, EGFR may be activated by many other factors such as angiotensin II, endothelin-1, catecholamines, and aldosterone; the phenomenon is referred to as “transactivation.” Several mechanisms of EGFR transactivation have been described among which two are the most important: (i) stimulation of metalloprotease-dependent cleavage of HB-EGF from its inactive membrane-bound precursor and (ii) direct phosphorylation of intracellular EGFR domain by c-Src. Transactivation of EGFR by these factors has been observed in blood vessels and the kidney and may contribute to the development of arterial hypertension by increasing vascular tone and/or tubular Na + reabsorption [38]. Indeed, EGFR inhibitors such as AG1478 reduce vascular tone and blood pressure in several experimental models of hypertension [38, 39].…”
Section: Pparγ-c-src-egfr-erk Pathwaymentioning
confidence: 99%
“…This observation is noteworthy as the epidermal growth factor receptor (EGFR) may contribute to the development of hypertension by regulating vascular tone and renal sodium handling [51]. Synthetic EGFR inhibitors also reduce blood pressure in some experimental models of hypertension and have been suggested as a novel target for antihypertensive therapy [52].…”
Section: Discussionmentioning
confidence: 99%
“…It has been more recently reported that EGFR activation may contribute to the development of hypertension by regulating vascular tone and renal sodium handling [21]. Hence EGFR inhibitors have been used to reduce blood pressure in experimental models of hypertension, suggesting that EGFR is a novel target for salt sensitive hypertension [24]. We have previously demonstrated that EGF and high-glucose-induced NHE3 expression and activity in the proximal tubule is EGFR dependent with downstream activation of Sgk1 [1].…”
Section: Discussionmentioning
confidence: 99%
“…EGFRs have been recognised as key targets in anticancer therapy and EGFR inhibitors are increasingly used in the treatment of cancer with no reported renal toxicity, despite such patients being at increased risk of acute renal injury, predominantly due to sepsis. The major side effect of targeting the EGFR clinically is inflammatory reactions in the skin [24]. Hence targeting the EGFR in combination with the PPAR γ agonist has the potential to be beneficial in regulating nephromegaly, matrix expansion, and fibrosis in addition to excessive sodium reabsorption observed in diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%